2018
DOI: 10.1002/jemt.23060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemical and morphological changes in radicular dentin after different final surface treatments

Abstract: The aim of this study was to evaluate the chemical and morphological effects of different lasers as a final surface treatment for endodontic therapy through energy dispersive X‐ray spectroscopy (EDS) and scanning electron microscopy (SEM) respectively. Twenty‐five maxillary canines were selected and instrumented with K3 system. Roots were randomly distributed into five groups (n = 5) according to the surface treatment: GI (distilled water), GII (NaOCl + EDTA), GIII (NaOCl + EDTA + 980 nm diode laser), GIV (NaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
4
1
3
Order By: Relevance
“…[ 24 ] The images generated by SEM are easily interpreted, despite the complexity of the mechanisms to obtain them. [ 24 ] Several studies used SEM and EDX analysis to evaluate dentin ultrastructure after different protocols for surface treatment,[ 22 23 ] and consistent findings were demonstrated, proving the efficacy of these methods.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[ 24 ] The images generated by SEM are easily interpreted, despite the complexity of the mechanisms to obtain them. [ 24 ] Several studies used SEM and EDX analysis to evaluate dentin ultrastructure after different protocols for surface treatment,[ 22 23 ] and consistent findings were demonstrated, proving the efficacy of these methods.…”
Section: Discussionmentioning
confidence: 88%
“…SEM is a versatile observational method. It can be used for the analysis of the microstructure of solid material, such as dentin,[ 22 23 ] and visualization of the interface of several materials to dental tissues. [ 24 ] The images generated by SEM are easily interpreted, despite the complexity of the mechanisms to obtain them.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In addition, some authors have reported melting and solidification of Er,Cr:YSGG laser irradiated dentin. 28,29 These morphological alternations might negatively affect resin hybridization. 30 During dentin laser irradiation, heat is generated, resulting in thermal denaturation of the collagen, breaking of the hydrogen bonds, and three-polypeptide chains in a triple helical molecular structure, which results in an irreversible transformation and shrinkage of the collagen fiber network.…”
Section: Discussionmentioning
confidence: 99%
“…La espectrofotometría Raman se puede utilizar para evaluar la estabilidad química de la dentina frente a diferentes tipos de tratamiento 99 . La EDS por su parte, es un método asociado a menudo al uso de MEB, ya que permite la valoración cualitativa de las superficies tratadas, como, por ejemplo, después de utilizar diferentes protocolos de riego o utilizar láser 100 . Además, la Micro-CT se puede utilizar para evaluar el espesor del cemento y la presencia de huecos, el espesor de la dentina, y para mejorar el procedimiento de remoción de pernos, entre otras aplicaciones [101][102][103] .…”
Section: Empleo De Las Técnicas En Las Investigaciones De Los Dientes Tratados Endodónticamenteunclassified